2015
DOI: 10.1021/acsnano.5b04070
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Fluctuations Act as Quantum Dot-like Emitters in GaAs-AlGaAs Core–Shell Nanowires

Abstract: GaAs-AlxGa1-xAs (AlGaAs) core-shell nanowires show great promise for nanoscale electronic and optoelectronic devices, but the application of these nonplanar heterostructures in devices requires improved understanding and control of nanoscale alloy composition and interfaces. Multiple researchers have observed sharp emission lines of unknown origin below the AlGaAs band edge in photoluminescence (PL) spectra of core-shell nanowires; point defects, alloy composition fluctuations, and self-assembled quantum dots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 34 publications
9
61
0
1
Order By: Relevance
“…The QD potential well is simplified as pure GaAs in order to use the experimental values in [13] and because the exact band structure of WZ AlGaAs is still a matter of debate [38][39][40]. The potential barrier is set by Al 0.2 Ga 0.8 As, in agreement with the experimental Al fluctuations in the shell away from the Al-rich ridges [27,33]. The QD width is chosen in agreement with previous studies [26,27,41].…”
Section: Experimental Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The QD potential well is simplified as pure GaAs in order to use the experimental values in [13] and because the exact band structure of WZ AlGaAs is still a matter of debate [38][39][40]. The potential barrier is set by Al 0.2 Ga 0.8 As, in agreement with the experimental Al fluctuations in the shell away from the Al-rich ridges [27,33]. The QD width is chosen in agreement with previous studies [26,27,41].…”
Section: Experimental Methodsmentioning
confidence: 97%
“…On the right: PL spectra (not normalized) from the positions indicated by the dashed vertical lines in the contour plot. extensively reported to be spatially non-uniform, with Al-rich planes at the ridge between two NW facets [26][27][28]33]. By changing the deposition time of the AlGaAs shell we grew three different samples with nominal shell thickness of 30 , 50 , and 100 nm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The latter was demonstrated in, e.g., GaP/Ga(As x P 1-x ) [1], In(Ga)As/GaAs [10], In(As x P 1-x )/InP [3,7], and GaAs/(Al x Ga 1-x )As [8] material systems. In addition, it was found that in GaAs/(Al x Ga 1-x )As NWs the QDs can be formed in the (Al x Ga 1-x )As region due to variations in the Al content [6,15]. Independent of the specific mechanism for the QD formation, the majority of such hybrid NW/QD systems utilize heterostructure design and, therefore, often experience strain caused by lattice mismatch between the involved materials.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers on the right indicate the excitation power in mW. The solid and dotted lines show the results of a fit using Eq (14). in Ref 29.…”
mentioning
confidence: 99%